Association of leisure-time physical activity with total and cause-specific mortality: a pooled analysis of nearly a half million adults in the Asia Cohort Consortium. (27th February 2018) - Liu, Ying; Shu, Xiao-Ou; Wen, Wanqing; Saito, Eiko; Rahman, M Shafiur; Tsugane, Shoichiro; Tamakoshi, Akiko; Xiang, Yong-Bing; Yuan, Jian-Min; Gao, Yu-Tang; Tsuji, Ichiro; Kanemura, Seiki; et al.
Abstract: Background: Most previous studies evaluating the association between leisure-time physical activity (LTPA) and risk of death were conducted among generally healthy individuals of European ancestry. We investigated the association of LTPA with all-cause and cause-specific mortality among East Asian populations, including healthy individuals and those with existing chronic diseases, which has been less well characterized. Methods: We performed pooled analyses among 467 729 East Asian individuals recruited in nine prospective cohorts included in the Asia Cohort Consortium. Cox proportional hazards regressions were used to derive hazard ratios (HRs) and 95% confidence intervals (CIs) associated with LTPA after adjusting for age, sex, education and marital and smoking status. Results: During a mean follow-up period of 13.6 years, 65 858 deaths were identified. Compared with those who reported no or less than 1 h of LTPA per week, an inverse association was observed between the amount of LTPA and all-cause and cause-specific mortality ( P for trend < 0.001). The strength of the inverse association was stronger for death due to cardiovascular diseases and causes other than cancer deaths. An inverse association of LTPA with total mortality was observed among individuals with a severe and often life-threatening disease: cancer, stroke or coronary heart disease [hazard ratio (HR) = 0.81, 95% CI = 0.73-0.89 for high vs low LTPA) and those with other chronic diseases such as diabetes or hypertension (HR = 0.86, 95% CI = 0.80-0.93 for high vs low LTPA). No clear modifying effects by sex, body mass index or smoking status were identified. Conclusions: Regular participation in LTPA is associated with reduced mortality in middle-aged and elder Asians regardless pre-existing health conditions.